One-Year Outcomes of Acute Decompensated Systolic Heart Failure in Taiwan: Lessons from TSOC-HFrEF Registry - Chang, Hung-Yu (Acta Cardiol Sin, 2017)
BACKGROUND: Heart failure (HF) is a global health problem. The Taiwan Society of Cardiology-Heart Failure with reduced Ejection Fraction (TSOC-HFrEF) registry was a multicenter, observational survey of patients admitted with HFrEF in Taiwan. The aim of this study was to report the one-year outcome in this large-cohort of hospitalized patients presenting with acute decompensated HFrEF. METHODS: Patients hospitalized for acute HFrEF were recruited in 21 hospitals in Taiwan. A total of 1509 patients were enrolled into the registry by the end of October 2014. Clinical status, readmission rates and dispensed medications were collected and analyzed 1 year after patient index hospitalization. RESULTS: Our study indicated that re-hospitalization rates after HFrEF were 31.9% and 38.5% at 6 and 12 months after index hospitalization, respectively. Of these patients, 9.7% of them were readmitted more than once. At 6 and 12 months after hospital discharge, all-cause mortality rates were 9.5% and 15.9%, respectively, and cardiovascular mortality rates were 6.8% and 10.5%, respectively. Twenty-three patients (1.5%) underwent heart transplantation. During a follow-up period of 1 year, 46.4% of patients were free from mortality, HF re-hospitalization, left ventricular assist device use and heart transplantation. At the conclusion of follow-up, 57.5% of patients were prescribed either with angiotensin-converting enzyme inhibitors or angiotensin receptor blockers; also, 66.3% were prescribed with beta-blockers and 40.8% were prescribed with mineralocorticoid receptor antagonists. CONCLUSIONS: The TSOC-HFrEF registry showed evidence of suboptimal practice of guideline-directed medical therapy and high HF re-hospitalization rate in Taiwan. The one-year mortality rate of the TSOC-HFrEF registry remained high. Ultimately, our data indicated a need for further improvement in HF care.